O ARROZ DE VENEZA E OS TRABALHADORES DE GUINÉ: A lavoura de exportação do Estado do Maranhão e Piauí (1770-1800) - Junior, Reinaldo dos Santos Barroso (Outros Tempos: Pesquisa em Foco - História, 2011)
The territory of  Maranhão, during  the colonial  period, was a major  producer andexporter of rice, especially in  the last quarter of  the eighteenth  century. The productionof rice was made possible by Africans of  the Upper Guinea, West  African territory. The  fame ofthese Africans as skilled producers of rice Oryza glaberrima (African  rice)  extendedfrom across the Atlantic - this was apparently specific knowledge of the cultivation of this cereal thatexcited the interest  of farmers and  government  officials in different localities. Maranhãoimported from  port of  Bissau, Cacheu and nearby, a lot of  these Africans by  virtue of  this apparentqualification on rice  production. The large-scale production of rice in the  state ofMaranhao and Piaui, in the second  half of  the  eighteenth  century, symbolizes the qualificationof guineensis and the importance of Africans to export project implemented in the colonies.